The Effect of Flow Rate on Morphology and Deposition Area of Electrospun Nylon 6 Nanofiber - Zargham, Shamim; Bazgir, Saeed; Tavakoli, Amir; Rashidi, Abo Saied; Damerchely, Rogheih (Journal of engineered fibers and fabrics, 2012)
Electrospinning is a process that produces continuous polymer fibers with diameters of a nanometric scale. Nylon 6 in formic acid was electrospun to obtain the nanofibers. Fibers with different diameters were obtained using flow rates of 0.1, 0.5, 1 and 1.5 mL/hr, 20 wt% solution concentration, with an applied voltage of 20 kV and 15 cm spinning distance. Flow rate influenced the fiber diameter distribution, droplet size and its initiating shape at the capillary tip, the trajectory of the jet, maintenance of Taylor cone, areal density and nanofiber morphology. The morphology of the electrospun nanofibers was analyzed by using the scanning electron microscope (SEM). The effect of flow rate on the deposition area was also investigated for better control of the process. It was observed that a stabilized Taylor cone, small average droplet size, narrowest fiber diameter distribution, more stability in the originating jet, and uniform morphology of nanofiber is obtained at a flow rate of 0.5 mL/hr.